FRI0217 SENSITIVITY AND SPECIFICITY OF 2019 DCVAS DRAFT CLASSIFICATION CRITERIA FOR GIANT CELLS ARTERITIS AND TAKAYASU ARTERITIS IN A MONOCENTRIC COHORT OF PATIENTS WITH CLINICAL DIAGNOSIS OF LARGE VESSEL VASCULITIS. (2nd June 2020) - Regola, F.; Tincani, A.; Franceschini, F.; Toniati, P.
Abstract : Background: Recently, a new set of classification criteria for Giant Cells Arteritis (GCA) and Takayasu Arteritis (TA) has been developed by the DCVAS project and presented as draft criteria at the 19th International Vasculitis and ANCA Workshop held in Philadelphia in 2019. Objectives: The purpose of the present study is to analyze the performance of the 2019 DCVAS Draft Classification Criteria in differentiating GCA and TA in a cohort of patients with Large Vessel Vasculitis (LVV), comparing their sensitivity and specificity to 1990 ACR Classification Criteria. Methods: 2019 DCVAS Draft Criteria and 1990 ACR Criteria were retrospectively applied to a cohort of 130 consecutive patients with Large Vessel Vasculitis. In all patients the diagnosis of vasculitis was histologically and/or radiologically confirmed. Results: One-hundred patients had a clinical diagnosis of GCA, 25 patients of TA and 5 patients of other form of LVV, different from GCA and TA (idiopathic isolated aortitis n:2, aortitis with retroperitoneal fibrosis n:2, isolated pulmonary arteritis n:1). Among the 100 patients clinically diagnosed as GCA (F/M: 68/32, age: 74 (60-83)) only 82 fulfilled the 1990 ACR Criteria for GCA, while all of them fulfilled the 2019 DCVAS Draft Criteria for GCA. Instead, among the 25 patients with a clinical diagnosis of TA (F/M: 21/4, age: 34 (16-48)), 22 (88%) could be classified as TA according to the 1990 ACR Criteria, 25 (100%) according to 2019 DCVAS Draft Criteria. In the group of patients diagnosed with other form of LVV (F/M: 2/3, age: 56 (38-71)) 4 patients (80%) fulfilled the 2019 DCVAS Draft Criteria for GCA, while none of them fulfilled the 2019 DCVAS Draft Criteria for TA or the 1990 ACR Criteria for GCA or TA. One of these patients did not fulfilled any classification criteria. On the contrary, one GCA patient could be classified both as GCA or TA according to the 2019 DCVAS Draft Criteria but didn't fulfilled the 1990 ACR Criteria for GCA or TA. For GCA, 2019 DCVAS Draft Criteria shown a sensitivity of 100% and a specificity of 80%, compared to 82% and 100% of 1990 ACR Criteria. For TA, 2019 DCVAS Draft Criteria shown a sensitivity of 100% and a specificity of 99%, compared to 88% and 100% of 1990 ACR Criteria. For GCA the agreement between the two different sets of criteria was 85.5% (Cohen's k coefficient: 0.64), for TA the agreement was 85.1% (k: 0.58). Conclusion: The new draft classification criteria shown a lower specificity if compared to the older ones, but also a higher sensitivity: in particular 2019 DCVAS Draft Criteria can better identify GCA patients with extracranial involvement, historically excluded from the 1990 ACR criteria. both GCA and TA 2019 DCVAS Draft Criteria, demonstrating that this classification well performs in differentiating GCA and TA. Disclosure of Interests: None declared